(untitled) (Praxis Educativa, 2014)
A significant number of investigations have enriched the historical knowledge of how students learn and which are the approaches to teaching in academia. Unlike other research, we set out to use academic biographies as a tool to: 1) learn about barriers and strengths in the learning that was built by students of the faculty during the academic career; and 2) as a communicational mediator to discuss, plan and rethink their pedagogical training approaches. This action research, allowed us to meet and reflect on the experiences of University students in which barriers and strengths live on. Our social concern as trainers of trainers is that barriers persist and are obstacles to obtain learning that is integrated and applied to life. If these barriers are not parsed in university teacher training, they will continue favoring the replication of rote learning, an approach opposite to that we intend.